Genotyping of carbapenem resistant Acinetobacter baumannii isolated from tracheal tube discharge of hospitalized patients in intensive care units, Ahvaz, Iran - Shoja, Saeed (Iran J Microbiol, 2013)
BACKGROUND AND OBJECTIVES: Carbapenem resistant A. baumannii is an emerging cause of nosocomial infections. The aims of this study were identification of the most prevalent of carbapenem resistant genes, molecular typing and antimicrobial evaluation of A.baumannii in intensive care units. MATERIALS AND METHODS: Two hundred and six A. baumannii were isolated from tracheal tube discharge of hospitalized patients at different intensive care units in Ahvaz, Iran. Antimicrobial susceptibility test was done on all isolates. Multiplex and singleplex PCR were performed for detection of bla(OXA-23-like), bla(OXA-24-like,) bla(OXA-51-like), bla(OXA-58-like), bla(VIM), bla(IMP), bla(SPM) and bla(NDM) genes. Genetic relationship of all isolates was determined by REP-PCR method. RESULTS: Out of 206 examined isolates, 198 (96.1%) isolates were resistant to imipenem and meropenem. However 3.9% isolates were sensitive to these antibiotics. The bla(OXA-23-like) and bla(OXA-24-like) genes were detected in 85% and 8.7% of strains, respectively. No bla(OXA-58- like), bla(IMP), bla(VIM), bla(SPM) and bla(NDM) were detected. REP-PCR results showed that isolates were belonged to five genotypes: Genotype A was the most prevalent (P- value < 0.001): it was observed in 75 of 206 strains (36.4%). Genotype B, and C were found in 28.6% and 27.7%, respectively. The rate of other genotypes was as follows: D (2.4%), E (1%). CONCLUSION: Based on the obtained results, the rate of carbapenem resistance was high among of A. baumannii which was isolated from intensive care units patients and oxacillinase genes were the most prevalent carbapenem resistant genes. These results revealed that three clones, A, B and C of A.baumannii are common in our hospitals.